The Urgency Of Studying Philosophy And Its Scope - Zidna Fahma (DIROSAT: Journal of Education, Social Sciences & Humanities, 2023)
The aim of this research is to explain the importance of studying philosophy, scope, figures and branches of philosophy. This research is a type of library research, research whose object of study uses a bibliography in the form of books, journals, articles as data sources. The characteristics of philosophical thinking are: descriptive, critical and analytical, evaluative or normative, speculative and systematic. So, philosophy can generally be interpreted as a science that investigates everything that exists to obtain the ultimate truth. The scope of philosophy is logic, aesthetics, ethics and metaphysics